Intracranial Hypertension and Papilledema in a Large Cohort of Pediatric Patients With Alagille Syndrome. Issue 5 (November 2020) - Rock, Nathalie M.; Demaret, Tanguy; Stéphenne, Xavier; Scheers, Isabelle; Smets, Francoise; McLin, Valérie A.; Boschi, Antonella; Sokal, Etienne M.
ABSTRACT: Aims and Background: Ophthalmic abnormalities are amongst the 5 major criteria required for a diagnosis of Alagille syndrome (ALGS), of which embryotoxon, pseudopapilledema, and hypopigmented retinopathy are the most common. Papilledema with or without intracranial hypertension (ICHT) is rarely described. We report 9 pediatric cases of ALGS with bilateral papilledema, 5 of which were diagnosed with ICHT. Methods: The ophthalmic data from 85 patients with clinically and/or genetically (n = 37) proven ALGS were reviewed. The study inclusion criteria were a positive diagnosis of ALGS and availability of ophthalmic follow-up data. Ophthalmic data from 40 patients after liver transplantation (LT) for other indications were also analyzed. Results: Nine (13.0%) of the 69 patients meeting the inclusion criteria had papilledema. The neurological and neuroimaging results in all 9 patients were normal. These 9 patients were categorized into 4 groups: a nontransplant group (n = 1), a group with pretransplant papilledema persistent after LT (n = 2), a group with papilledema occurring after LT with spontaneous resolution (n = 1), and a group with papilledema and signs of ICHT after LT (n = 5). The patients with ICHT were treated with steroids alone (n = 1) or with acetazolamide (n = 4). A ventriculoperitoneal shunt was placed in 2 of the 5 cases because of progressive visual loss. Pseudopapilledema was present in 10 additional patients (14.5%, 10/69). One (2.5%) of the 40 patients without ALGS developed papilledema after LT. Conclusions: True ICHT may be underdiagnosed in patients with ALGS. Our findings underscore the need for close ophthalmic follow-up before and after LT in these patients.